The temperature sensitivity of ecosystem respiration to climate change in an alpine meadow on the Tibet plateau: A reciprocal translocation experiment - Hu, Yigang; Jiang, Lili; Wang, Shiping; Zhang, Zhenhua; Luo, Caiyun; Bao, Xiaoying; Niu, Haishan; Xu, Guangping; Duan, Jichuang; Zhu, Xiaoxue; Cui, Shujuan; Du, Mingyuan (Agricultural and forest meteorology, 2016)
•Warming increased and cooling decreased ecosystem respiration (Re).•Re at the higher elevation was more sensitive than that at lower elevation.•The temperature sensitivity of Re to warming and to cooling was asymmetrical. Information about the potential effects of climate change, especially cooling, on ecosystem respiration (Re) in alpine meadows is scarce. We determined the effects of warming and cooling on Re on the Tibetan Plateau using a 2-year reciprocal translocation experiment with 4 different vegetation types (3 alpine meadows and 1 alpine shrub differentiated by plant community composition) along an elevation gradient from 3200 to 3800m (with vegetation types E2, E4, E6 and E8 at 3200, 3600, 3800 and 3800m, respectively) during the growing seasons in 2008 and 2009. Mean growing seasonal Re decreased by 13.6, 30.3 and 40.7% per 200m rise in elevation (cooling) for vegetation types E2, E4 and E6, but increased by 1.3, 35.9 and 58.8% per 200m decrease in elevation (warming) for vegetation types E4, E6 and E8, respectively. Soil temperature explained 49.3–64.0% of daily Re variation and aboveground biomass explained 21.5–61.6% of average Re variation of the growing season for all vegetation types, but the effect of soil moisture on Re was small over 2-year. The values of Re temperature sensitivity increased with an increase in elevation for both warming (3.3, 24.3 and 53.5%°C−1 for vegetation types E4, E6 and E8) and cooling (8.0, 19.1 and 24.4%°C−1 for vegetation types E2, E4 and E6), suggesting that alpine meadow at higher elevation was more sensitive to both warming and cooling. Based on the values of Re temperature sensitivity for all pooled vegetation types (25.4, 5.6 and 19.6%°C−1 for warming, cooling and pooled warming and cooling), it could be over-estimated by 23% for warming alone compared with pooled warming and cooling. Therefore, asymmetrical responses of Re to warming and cooling should be taken into account when we evaluate the effect of temperature change on Re using models in the future.